2012
DOI: 10.1371/journal.pone.0032864
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights from Binding Poses of CCR2 and CCR5 with Clinically Important Antagonists: A Combined In Silico Study

Abstract: Chemokine receptors are G protein-coupled receptors that contain seven transmembrane domains. In particular, CCR2 and CCR5 and their ligands have been implicated in the pathophysiology of a number of diseases, including rheumatoid arthritis and multiple sclerosis. Based on their roles in disease, they have been attractive targets for the pharmaceutical industry, and furthermore, targeting both CCR2 and CCR5 can be a useful strategy. Owing to the importance of these receptors, information regarding the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 69 publications
1
32
1
Order By: Relevance
“…Recently, we compared the binding sites of CCR2 and CCR5 to facilitate the development of dual antagonists targeting both CCR2 and CCR5. 58 In the present study, we found that Ser101 is important for CCR2 antagonism from our initial rigid docking study. However, the dynamic process showed that 4AAC derivative moved away from Ser101 and the hydrogen bond vanished.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Recently, we compared the binding sites of CCR2 and CCR5 to facilitate the development of dual antagonists targeting both CCR2 and CCR5. 58 In the present study, we found that Ser101 is important for CCR2 antagonism from our initial rigid docking study. However, the dynamic process showed that 4AAC derivative moved away from Ser101 and the hydrogen bond vanished.…”
Section: Discussionsupporting
confidence: 49%
“…25,[58][59][60][61] In particular, we have developed 3D-QSAR models for CCR2 using ligand based and receptor guided methodologies. 25 In this study, we used Teijin derivatives 23 to derive CoMFA and CoMSIA models, and we found that Ala102 and Asn207 are probably crucial for activity.…”
Section: Discussionmentioning
confidence: 99%
“…We have been working on GPCR's using in silico methodologies [34][35][36] and we moved our focus on NOPR. Previously there were reports on homology modeling of NOPR.…”
Section: Discussionmentioning
confidence: 99%
“…This motif is situated at the 3 0 end of second external loop. In Human, this particular CCR5 region was found to provide binding pockets for a variety of chemokine agonists and antagonists (Rucker et al 1997, Vassart et al 1996Samson Samson et al 1997;Paterlini 2002;Kothandan et al 2012). Residues at positions 194 and 198 of CCR5 have been associated with lentivirus interactions, such as HIV (Ribeiro et al 2005).…”
Section: Introductionmentioning
confidence: 99%